Entrance to the Garbhagriha of the Someshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The entrance to the garbhagriha (sanctum sanctorum) of the Someshwar Mahadev Temple is marked by an ornate dvarashakha (door jamb). The uttaranga (top band) of the dvarashakha and the vertical divisions flanking the opening have depictions of deities like Shiva, Mahesh, Brahma, and goddesses.